Difference between revisions of "009A Sample Midterm 3, Problem 1"

From Math Wiki
Jump to navigation Jump to search
 
(2 intermediate revisions by the same user not shown)
Line 7: Line 7:
 
<span class="exam">(c) Evaluate &nbsp;<math style="vertical-align: -16px">\lim _{x\rightarrow \infty} \frac{-2x^3-2x+3}{3x^3+3x^2-3}. </math>
 
<span class="exam">(c) Evaluate &nbsp;<math style="vertical-align: -16px">\lim _{x\rightarrow \infty} \frac{-2x^3-2x+3}{3x^3+3x^2-3}. </math>
  
 +
<hr>
 +
[[009A Sample Midterm 3, Problem 1 Solution|'''<u>Solution</u>''']]
  
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Foundations: &nbsp;
 
|-
 
|'''1.''' If &nbsp;<math style="vertical-align: -13px">\lim_{x\rightarrow a} g(x)\neq 0,</math>&nbsp; we have
 
|-
 
|&nbsp; &nbsp; &nbsp; &nbsp; <math>\lim_{x\rightarrow a} \frac{f(x)}{g(x)}=\frac{\displaystyle{\lim_{x\rightarrow a} f(x)}}{\displaystyle{\lim_{x\rightarrow a} g(x)}}.</math>
 
|-
 
|'''2.''' Recall
 
|-
 
|&nbsp; &nbsp; &nbsp; &nbsp;<math style="vertical-align: -15px">\lim_{x\rightarrow 0} \frac{\sin x}{x}=1</math>
 
|}
 
  
 +
[[009A Sample Midterm 3, Problem 1 Detailed Solution|'''<u>Detailed Solution</u>''']]
  
'''Solution:'''
 
  
'''(a)'''
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Step 1: &nbsp;
 
|-
 
|First, we have
 
|-
 
|&nbsp; &nbsp; &nbsp; &nbsp; <math>\begin{array}{rcl}
 
\displaystyle{2} & = & \displaystyle{\lim_{x\rightarrow 3} \bigg(\frac{f(x)}{2x}+1\bigg)}\\
 
&&\\
 
& = & \displaystyle{\lim_{x\rightarrow 3} \frac{f(x)}{2x}+\lim_{x\rightarrow 3} 1}\\
 
&&\\
 
& = & \displaystyle{\lim_{x\rightarrow 3} \frac{f(x)}{2x}+1.}
 
\end{array}</math>
 
|-
 
|Therefore,
 
|-
 
|&nbsp; &nbsp; &nbsp; &nbsp; <math>\lim_{x\rightarrow 3} \frac{f(x)}{2x}=1.</math>
 
|}
 
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Step 2: &nbsp;
 
|-
 
|Since &nbsp;<math style="vertical-align: -13px">\lim_{x\rightarrow 3} 2x=6\ne 0,</math>&nbsp; we have
 
|-
 
|
 
&nbsp; &nbsp; &nbsp; &nbsp; <math>\begin{array}{rcl}
 
\displaystyle{1} & = & \displaystyle{\lim_{x\rightarrow 3} \frac{f(x)}{2x}}\\
 
&&\\
 
& = & \displaystyle{\frac{\displaystyle{\lim_{x\rightarrow 3} f(x)}}{\displaystyle{\lim_{x\rightarrow 3} 2x}}}\\
 
&&\\
 
& = & \displaystyle{\frac{\displaystyle{\lim_{x\rightarrow 3} f(x)}}{6}.}
 
\end{array}</math>
 
|-
 
|Multiplying both sides by &nbsp;<math style="vertical-align: -5px">6,</math>&nbsp; we get
 
|-
 
|&nbsp; &nbsp; &nbsp; &nbsp; <math>\lim_{x\rightarrow 3} f(x)=6.</math>
 
|}
 
 
'''(b)'''
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Step 1: &nbsp;
 
|-
 
|First, we write
 
|-
 
|&nbsp; &nbsp; &nbsp; &nbsp; <math>\begin{array}{rcl}
 
\displaystyle{\lim_{x\rightarrow 0} \frac{\tan(4x)}{\sin(6x)}} & = & \displaystyle{\lim_{x\rightarrow 0} \frac{\sin(4x)}{\cos(4x)} \frac{1}{\sin(6x)}}\\
 
&&\\
 
& = & \displaystyle{\lim_{x\rightarrow 0} \frac{4}{6} \frac{\sin(4x)}{4x}\frac{6x}{\sin(6x)}\frac{1}{\cos(4x)}}\\
 
&&\\
 
& = & \displaystyle{\frac{4}{6}\lim_{x\rightarrow 0} \frac{\sin(4x)}{4x}\frac{6x}{\sin(6x)}\frac{1}{\cos(4x)}.}
 
\end{array}</math>
 
|}
 
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Step 2: &nbsp;
 
|-
 
|Now, we have
 
|-
 
|
 
&nbsp; &nbsp; &nbsp; &nbsp; <math>\begin{array}{rcl}
 
\displaystyle{\lim_{x\rightarrow 0} \frac{\tan(4x)}{\sin(6x)}} & = & \displaystyle{\frac{4}{6}\lim_{x\rightarrow 0} \frac{\sin(4x)}{4x}\frac{6x}{\sin(6x)}\frac{1}{\cos(4x)}}\\
 
&&\\
 
& = & \displaystyle{\frac{4}{6}\bigg(\lim_{x\rightarrow 0} \frac{\sin(4x)}{4x}\bigg)\bigg(\lim_{x\rightarrow 0} \frac{6x}{\sin(6x)}\bigg)\bigg(\lim_{x\rightarrow 0} \frac{1}{\cos(4x)}\bigg)}\\
 
&&\\
 
& = & \displaystyle{\frac{4}{6} (1)(1)(1)}\\
 
&&\\
 
& = & \displaystyle{\frac{2}{3}.}
 
\end{array}</math>
 
|}
 
 
'''(c)'''
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Step 1: &nbsp;
 
|-
 
|First, we have
 
|-
 
|&nbsp; &nbsp; &nbsp; &nbsp; <math>\begin{array}{rcl}
 
\displaystyle{\lim _{x\rightarrow \infty} \frac{-2x^3-2x+3}{3x^3+3x^2-3}} & = & \displaystyle{\lim _{x\rightarrow \infty} \frac{(-2x^3-2x+3)}{(3x^3+3x^2-3)} \frac{(\frac{1}{x^3})}{(\frac{1}{x^3})}}\\
 
&&\\
 
& = & \displaystyle{\lim_{x\rightarrow 0} \frac{-2-\frac{2}{x^2}+\frac{3}{x^3}}{3+\frac{3}{x}-\frac{3}{x^3}}}.
 
\end{array}</math>
 
|}
 
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Step 2: &nbsp;
 
|-
 
|Now, we use the properties of limits to get
 
|-
 
|
 
&nbsp; &nbsp; &nbsp; &nbsp; <math>\begin{array}{rcl}
 
\displaystyle{\lim _{x\rightarrow \infty} \frac{-2x^3-2x+3}{3x^3+3x^2-3}} & = & \displaystyle{\lim_{x\rightarrow \infty} \frac{-2-\frac{2}{x^2}+\frac{3}{x^3}}{3+\frac{3}{x}-\frac{3}{x^3}}}\\
 
&&\\
 
& = & \displaystyle{\frac{\lim_{x\rightarrow \infty} (-2-\frac{2}{x^2}+\frac{3}{x^3})}{\lim_{x\rightarrow \infty} (3+\frac{3}{x}-\frac{3}{x^3})}}\\
 
&&\\
 
& = & \displaystyle{\frac{\lim_{x\rightarrow \infty} -2 +\lim_{x\rightarrow \infty} \frac{2}{x^2} +\lim_{x\rightarrow \infty} \frac{3}{x^3}}{\lim_{x\rightarrow \infty} 3+\lim_{x\rightarrow \infty} \frac{3}{x}-\lim_{x\rightarrow \infty}\frac{3}{x^3}}} \\
 
&&\\
 
& = & \displaystyle{\frac{-2+0+0}{3+0+0}}\\
 
&&\\
 
& = & \displaystyle{-\frac{2}{3}.}
 
\end{array}</math>
 
|}
 
 
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Final Answer: &nbsp;
 
|-
 
|&nbsp; &nbsp; '''(a)''' &nbsp; &nbsp; <math>6</math>
 
|-
 
|&nbsp; &nbsp; '''(b)'''  &nbsp; &nbsp; <math>\frac{2}{3}</math>
 
|-
 
|&nbsp; &nbsp; '''(c)''' &nbsp; &nbsp; <math>-\frac{2}{3}</math>
 
|}
 
 
[[009A_Sample_Midterm_3|'''<u>Return to Sample Exam</u>''']]
 
[[009A_Sample_Midterm_3|'''<u>Return to Sample Exam</u>''']]

Latest revision as of 14:23, 9 November 2017

Find the following limits:

(a) If    find  

(b) Find  

(c) Evaluate  


Solution


Detailed Solution


Return to Sample Exam